Penguatan Peran Non-Government Organisation (NGOs) Penggiat HIV/AIDS melalui Pelatihan Konselor di Kota Makassar - Rahman, Framita; Yusnitasari, Andi Selvi; Nurdin, Nurhaya; Yulia, Asti; Salsabila, Rezky; Syukur, Azzahra Marsha; Sahrir, Raidatul Zahidah; Yasmin MR, Ufahira (Jurnal Abdimas Kesehatan (JAK), 2025)
HIV/AIDS remains a global health issue that demands comprehensive action, including strengthening human resource capacity at the community level. This community engagement program aimed to enhance the role of Non-Governmental Organizations (NGOs) in HIV/AIDS prevention and management through counseling skills training conducted at the Faculty of Nursing, Hasanuddin University. Nine participants from five NGOs took part in the training, which covered topics such as HIV/AIDS knowledge, health literacy, and counseling practice simulations. Evaluation was carried out through pre- and post-tests, as well as direct observation. Results showed a notable increase in participants' knowledge and adequate counseling practice skills, although gaps remained in technical competencies such as psychosocial assessment and handling complex cases. Challenges included participant absenteeism and schedule delays, affecting program effectiveness. Further structured training is needed to optimize the capacity of community counselors to support people living with HIV/AIDS professionally and sustainably.